Experimental Studies of Thermoelectric Characteristics of Plastically Deformed Steels ST3, 08KP and 12H18N10T; Key Engineering Materials; Vol. 685 : High Technology: Research and Applications 2015 (HTRA 2015) - Soldatov A. I. Aleksey Ivanovich; Soldatov A. A. Andrey Alekseevich; Kostina M. A. Maria Alekseevna; Kozhemyak O. A. Olesya Anatolievna (Mechanical Engineering Technology, 2016)
Title screen